Nanoglomus plukenetiae, a new fungus from Peru, and a key to small-spored Glomeraceae species, including three new genera in the “Dominikia complex/clades” - Corazon-Guivin M.A. (2019)
A new arbuscular mycorrhizal fungus was found in an agricultural plantation of Plukenetia volubilis, the inka nut (also called “sacha inchi” or “inka peanut”) in the Amazonia region of San Martín State in Peru. In this site, the inka nut was grown in mixed cultures together with Zea mays and Phaseolus vulgaris. The fungus was propagated in bait and single-species cultures on Sorghum vulgare, Brachiaria brizantha, Medicago sativa, and Plukenetia volubilis as host plants. The fungus differentiates hyaline spores terminally or intercalary on cylindrical to slightly funnel-shaped hyphae, singly or in spore clusters with up to ca. 90 spores per cluster. The spores are bi-layered, (20–)25–36(–45) ?m in diameter and show regularly a visible septum at the spore base, despite the small spore and tiny hyphae sizes. Phylogenetically, the new fungus represents a new genus in a separated clade, near to the already known Dominikia clades. It can be distinguished from other species by the small spore size, the characteristics of the spore wall layers, and the clearly visible septum at the spore base, which in Kamienskia and Microkamienskia species has rarely to never been reported, while Dominikia species usually have a higher variability of spore sizes and spore wall characteristics. The fungus is here described under the epithet Nanoglomus plukenetiae, serving as type species of the new genus Nanoglomus. The revision of the species and environmental sequences in the Dominikia clades, based on both morphological and molecular phylogenetic analyses, revealed at least two other new genera: Microdominikia gen. nov., based on D. litorea, and Orientoglomus gen. nov., based on D. emiratia. Finally, in the present study, a key for all small-spored species in the Glomeraceae is included comprising all known Dominikia, Kamienskia, Microdominikia, Microkamienskia, Nanoglomus, Orientoglomus spp., and all small-spored Rhizoglomus spp. © 2019, German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature.